Considerations on the publication of decisions by ethics committees - Coronado Zarco, Irma Alejandra; Domínguez Márquez, Octaviano (Acta Bioethica, 2013)
This is an analysis about the form in which written communication can become a tool of influence and legitimacy for ethics committees. It stems from a historical revision of documents generated by diverse types of ethics committees which have had an influence on transcendental decisions on the medical, legal, and social spheres and proposes some factors to be considered in every document generated by committees in their activities as well as the scientific, medical, social, and legal contexts. This review and the historical analysis generate a list of functions for the diverse publications of ethics committees.